2006
DOI: 10.1128/jvi.80.3.1271-1279.2006
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analyses of RNA Structures Shared between the Internal Ribosome Entry Sites of Hepatitis C Virus and the Picornavirus Porcine Teschovirus 1 Talfan

Abstract: The internal ribosome entry site (IRES) of porcine teschovirus 1 (PTV-1), a member of the Picornaviridae family, is quite distinct from other well-characterized picornavirus IRES elements, but it displays functional similarities to the IRES from hepatitis C virus (HCV), a member of the Flaviviridae family. In particular, a dominant negative mutant form of eIF4A does not inhibit the activity of the PTV-1 IRES. Furthermore, there is a high level (ca. 50%) of identity between the PTV-1 and HCV IRES sequences. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
80
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 42 publications
4
80
0
Order By: Relevance
“…Mutations within the loop of domain IIIe strongly inhibited IRES function. Similarly, disruption of the pseudoknot inhibited IRES activity, and conversely, mutants inserting compensatory mutations in S1 and S2 stems displayed enhanced IRES function (Chard et al, 2006b).…”
Section: Picornavirus Ires Elements Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations within the loop of domain IIIe strongly inhibited IRES function. Similarly, disruption of the pseudoknot inhibited IRES activity, and conversely, mutants inserting compensatory mutations in S1 and S2 stems displayed enhanced IRES function (Chard et al, 2006b).…”
Section: Picornavirus Ires Elements Diversitymentioning
confidence: 99%
“…Concerning the HCV-like picornavirus IRES elements, early studies carried out on the PTV-1 IRES showed that the functional element spans only 280 nts (Chard et al, 2006b). A secondary structure model for the PTV-1 IRES (Chard et al, 2006b) predicted domains II and III, but in contrast to the HCV IRES, domain IV was lacking.…”
Section: Picornavirus Ires Elements Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Human picornaviruses produce symptoms ranging from mild respiratory illness to hemorrhagic conjunctivitis, myocarditis, acute flaccid paralysis, and neonatal organ failure (19,27,28,33,40,41). Veterinary picornaviruses, such as foot-and-mouth disease virus (FMDV), encephalomyocarditis virus (EMCV), and porcine teschovirus (PTV), can have devastating effects on livestock (5,8,21).…”
mentioning
confidence: 99%
“…Human picornaviruses produce symptoms ranging from mild respiratory illness to hemorrhagic conjunctivitis, myocarditis, acute flaccid paralysis, and neonatal organ failure (19,27,28,33,40,41). Veterinary picornaviruses, such as foot-and-mouth disease virus (FMDV), encephalomyocarditis virus (EMCV), and porcine teschovirus (PTV), can have devastating effects on livestock (5,8,21).Although picornaviruses such as poliovirus (PV) are known to evolve more rapidly than other viruses with single-stranded RNA (ssRNA) genomes (9, 29), little research has been conducted to investigate how they evolve more rapidly than other viruses with similarly error-prone RNA-dependent RNA polymerases (29, 57) or if certain picornaviruses evolve more rapidly than others. Understanding the evolutionary potentials and constraints of these important pathogens is imperative for the development of durable vaccines and effective treatment plans for individual pathogens (42).…”
mentioning
confidence: 99%